Evolution of Diaphragm Thickness during Mechanical Ventilation. Impact of Inspiratory Effort - Goligher, Ewan C.; Fan, Eddy; Herridge, Margaret S.; Murray, Alistair; Vorona, Stefannie; Brace, Debbie; Rittayamai, Nuttapol; Lanys, Ashley; Tomlinson, George; Singh, Jeffrey M.; Bolz, Steffen-Sebastian; Rubenfeld, Gordon D.; et al. (American journal of respiratory and critical care medicine, 2015)
Diaphragm atrophy and dysfunction have been reported in humans during mechanical ventilation, but the prevalence, causes, and functional impact of changes in diaphragm thickness during routine mechanical ventilation for critically ill patients are unknown. To describe the evolution of diaphragm thickness over time during mechanical ventilation, its impact on diaphragm function, and the influence of inspiratory effort on this phenomenon. In three academic intensive care units, 107 patients were enrolled shortly after initiating ventilation along with 10 nonventilated intensive care unit patients (control subjects). Diaphragm thickness and contractile activity (quantified by the inspiratory thickening fraction) were measured daily by ultrasound. Over the first week of ventilation, diaphragm thickness decreased by more than 10% in 47 (44%), was unchanged in 47 (44%), and increased by more than 10% in 13 (12%). Thickness did not vary over time following extubation or in nonventilated patients. Low diaphragm contractile activity was associated with rapid decreases in diaphragm thickness, whereas high contractile activity was associated with increases in diaphragm thickness (P = 0.002). Contractile activity decreased with increasing ventilator driving pressure (P = 0.01) and controlled ventilator modes (P = 0.02). Maximal thickening fraction (a measure of diaphragm function) was lower in patients with decreased or increased diaphragm thickness (n = 10) compared with patients with unchanged thickness (n = 10; P = 0.05 for comparison). Changes in diaphragm thickness are common during mechanical ventilation and may be associated with diaphragmatic weakness. Titrating ventilatory support to maintain normal levels of inspiratory effort may prevent changes in diaphragm configuration associated with mechanical ventilation.